Math

posted by .

Subtract(5a^3+3 b^3)-(2a^2b-4ab^2+3b^3+5a^3)=

• Math -

since there's a 5a^3 + 3b^3 top and bottom, they just disappear, and you are left with

-(2a^2b-4ab^2)

Similar Questions

1. math

Match the equation with the step needed to solve it. 1. 2m - 1 = 3m subtract m 2. 2m = 1 + m subtract 2 3. m - 1 = 2 subtract 1 4. 2 + m = 3 subtract 2m 5. -2 + m = 1 add 2 6. 3 = 1 + m add 1
2. math

Match the equation with the step needed to solve it. 1. 2m - 1 = 3m subtract m 2. 2m = 1 + m subtract 2 3. m - 1 = 2 subtract 1 4. 2 + m = 3 subtract 2m 5. -2 + m = 1 add 2 6. 3 = 1 + m add 1
3. math

How do you factor this completely? 4ab + 2a + 6b + 3
4. math

-8a^2+5ab-12a^2-6(2a^2-4ab-10n^2)
5. Math 8R - Help!!!!!!!!!!!!!!!!!!!

14. Subtract -5 from -14 -14 - (-5) 16. Subtract -6 from 18 18 - (-6) 18. From 14 subtract -2 22. Subtract 17 from 8 I already know how to solve this just have trouble formatting it. How do I do it for number 18 and 22?
6. Math

The expression (-2a^2b^3)(4ab^5)(6a^3b^2) can be simplified to what exponential espression